Assessment of vulnerability to climate change using indicators: a meta‐analysis of the literature. (9th September 2014) - Tonmoy, Fahim N.; El‐Zein, Abbas; Hinkel, Jochen
Abstract : Climate change vulnerability assessment (CCVA) can inform adaptation policy and help in incorporating climate futures in planning. The literature on CCVA stems from a number of research paradigms (e.g., risk assessment, natural disaster management, and urban planning), therefore making it difficult to extract major directions and methodologies from this body of work. A large number of assessments are based, partly or totally, on indicators which bring up specific methodological problems and constraints. In this study, first, we discuss the most important methodological challenges facing indicator‐based vulnerability assessment (IBVA) based on a set of key conceptual papers in the field. Second, we conduct a meta‐analysis of a representative sample of peer‐reviewed IBVA studies, to identify how current research on IBVA is engaging with these challenges. We attempt to elicit major thematic and methodological trends in this corpus with specific focus on issues related to geographical and temporal scales, aggregation, and nonlinearity. We find that health of ecosystems and biodiversity (28%), freshwater quantity and quality (12%), and public health (10%) have attracted the highest number of studies. Less than a third of the papers in our sample give some consideration to uncertainty and nonlinearity. Assessments typically use aggregation methods that are based on the Multiple Attribute Utility Theory despite the fact that IBVA rarely satisfies the theoretical requirements of this approach. A small percentage of IBVA studies critically scrutinize prevalent assessment methodologies or attempt to develop new ones, despite the raised questions in key theoretical papers about its methodological aspects. WIREs Clim Change 2014, 5:775–792. doi: 10.1002/wcc.314 This article is categorized under: Vulnerability and Adaptation to Climate Change > Values‐Based Approach to Vulnerability and Adaptation